Architectural-ecclesiological Ekphrasis in Literary studies - Mamadiyarova Yulduz (Euro Asian Journal Publishing, 2023)
The article discusses the issues of translating ekphrasis texts, as well as the interpretation of the term “religious ekphrasis” and the analysis of architectural and ecclesiological texts of ekphrasis. An analysis of the study of religious and architectural-ecclesiological ekphrasis by Russian and European scientists is noted.
Keywords: Ecclesiology; religious ekphrasis; ecclesiological ekphrasis; contamination